2019
DOI: 10.1128/aac.01979-18
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Biofilms Are Generally Devoid of Persister Cells

Abstract: Candida albicans is known for its ability to form biofilms, which are communities of microorganisms embedded in an extracellular matrix developing on different surfaces. Biofilms are highly tolerant to antifungal therapy. This phenomenon has been partially explained by the appearance of so-called persister cells, phenotypic variants of wild-type cells, capable of surviving very high concentrations of antimicrobial agents. Persister cells in C. albicans were found exceptionally in biofilms, while none were dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Persister cells were reported for the first time as a subpopulation of bacteria tolerant to a particular antibiotic that, after removal of the antimicrobial agent, gave rise to a new population of susceptible microbial cells (Bigger, 1944 ). In the clinical setting, persisters are usually associated with recurrent infections and the development of chronic infections (Denega et al, 2019 ). The first report of Candida spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persister cells were reported for the first time as a subpopulation of bacteria tolerant to a particular antibiotic that, after removal of the antimicrobial agent, gave rise to a new population of susceptible microbial cells (Bigger, 1944 ). In the clinical setting, persisters are usually associated with recurrent infections and the development of chronic infections (Denega et al, 2019 ). The first report of Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Al-Dhaheri and Douglas ( 2008 ) showed that not all Candida spp. and strains are able to form persister cells, for example, C. albicans strain SC5314 (Gillum et al, 1984 ), one of the most commonly used C. albicans strains used for molecular genetics studies, is not able to form persister cells in vitro (Denega et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antifungal persistence was associated with biofilms in one study, but it has been more difficult to detect (reviewed in ref. 43) and its relevance remains controversial 44 .…”
Section: Mechanisms Of Antifungal Resistance and Tolerancementioning
confidence: 99%
“…It will be important to see if this mechanism is also relevant in vivo, where glucose levels are often limited and greater competition for glucose, or co-utilization of alternative carbon sources, could be expected. The role of both bacterial persister cell in antibiotic resistance in the context of monomicrobial biofilms have been studied, however the role of C. albicans persister cells seem to be more controversial with different findings regarding the occurrence of persister cells in C. albicans biofilms (Denega et al, 2019;Galdiero et al, 2020b). However, the role of bacterial (or C. albicans) persister cells in polymicrobial biofilms, especially their influence on drug tolerance, has not been studied yet.…”
Section: Impact On Antimicrobial Resistancementioning
confidence: 99%